The Role of the Maker Movement in Engineering Education: Student Views on Key Issues of Makerspace Environment - (:unkn) unknown (TEMPUS PUBLICATIONS, 2020)
Makerspaces are becoming increasingly important as a new approach to enable individuals to experience new technology applications and increase creativity in universities and other educational institutions. Such learning implementations offer many advantages like learning-by-doing and applying theoretical knowledge in engineering education into practical skills in an interdisciplinary environment. Despite the advantages, makerspaces still lack integration into the curriculum of engineering schools. For a quality engineering education, establishing maker workshops where students can experiment, design and practice as well as feel encouraged to open-ended development projects are required in addition to standard theoretical and laboratory applications. In this study, we present student views on the learning opportunities, challenges and contributions of the makerspace environment. In this context, IHA Makerspace established within the Faculty of Technology, Marmara University, Turkey, aims to provide high-level engineering experience to students by designing and prototyping effectively in a multidisciplinary development environment.
Keywords: Makerspace; learning environment; engineering education; student views